College Students' Sense of Belonging: A National Perspective - Gopalan, Maithreyi; Brady, Shannon T. (Educational researcher, 2020)
In a nationally representative sample, first-year U.S. college students "somewhat agree," on average, that they feel like they belong at their school. However, belonging varies by key institutional and student characteristics; of note, racialethnic minority and first-generation students report lower belonging than peers at 4-year schools, while the opposite is true at 2-year schools. Further, at 4-year schools, belonging predicts better persistence, engagement, and mental health even after extensive covariate adjustment. Although descriptive, these patterns highlight the need to better measure and understand belonging and related psychological factors that may promote college students' success and well-being.